Recovery after exposure to high LET-radiation. - Kiefer, J. (Nature Publishing Group, 1984)
In many cellular systems the shape of survival curves is changed from a sigmoidal to a purely exponential type if the LET of the radiation is increased. This is often explained by the hypothesis that repair mechanisms are less effective or non-functional with lesions generated by densely ionizing radiation. The absence of split-dose sparing and/or recovery from potentially lethal damage is then taken as further support. A careful consideration has to take into account, however, that with particle exposure the pattern of energy deposition varies considerably within a cell population and that the actual distribution depends also on cell geometry. If one accepts the view that with low-LET radiations repair may be saturated at high dose, the survival curve shape characteristic of high LET may be explained by the assumption that in this case saturation may occur due to the energy deposited by one or few heavy charged particles. The absence of recovery would then be due to microdosimetric parameters rather than to the nature or pattern of the primary molecular lesions. This alternative can be tested quantitatively by comparative analysis of the survival behaviour of different cellular systems exposed to radiations of varying LET. Our experiments with yeast strains of different sensitivities show that recovery from potentially lethal damage can be demonstrated even after exposure to uranium ions. Quantitative analysis leads to the conclusion that the apparent reduction in the extent of recovery is mostly due to saturation at the cellular level rather than to non-reparability of the primary lesions or to destruction of the repair system.